MEMAHAMI FENOMENA RESILIENSI DAN CYBERBULLYING DI KALANGAN SISWA - Rulia Hanifah; Muhammad Buchori Ibrahim; Muhamad Antos Riady; Tamimi Mujahid (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This research study was conducted to understand the phenomenon of cyberbullying, which is becoming increasingly prevalent in various circles, including among students. In addition to cyberbullying, the study examined aspects related to student resilience. The study involved 150 student respondents from junior and senior high schools in the Aceh Province, primarily from Banda Aceh, Aceh Besar, Aceh Selatan, Pidie, and Bireuen. Using a quantitative approach, the sample was collected over six months at the beginning of 2025. Preliminary test results showed that the reliability test for the cyberbullying scale was 0.879, while the reliability test for the resilience scale was 0.910. The research findings revealed a negative relationship between resilience and cyberbullying, with a correlation coefficient of -0.176. This indicates that higher levels of resilience are associated with lower levels of cyberbullying. Descriptively, students in Aceh, at both the junior and senior high school levels, have a high level of resilience. This is reflected in the low prevalence of cyberbullying: 36.7% among junior high school students and 46% among senior high school students. The high cyberbullying category was only found among 2% of junior high school students, and not at all among senior high school students (0%). Keywords: resilience, cyberbullying, Student in Aceh